How much does it cost the river near my house? An integrated methodology to identify a value for ecosystemic services (The case of Vjosa Valley in Albania) - Kokthi, Elena; Guri, Fatmir; Shehu, Eneida; Sovinc, Andrej; Gura, Kriselda Sulcaj (Frontiers in Environmental Science, 2023)
This study aims to identify and evaluate ecosystem services and calculate the total economic value of Vjosa Valley, an endangered riverine ecosystem. An instrumental-deliberative approach is used with experts and Albania's general public. The results show that experts highly evaluate Vjosa Valley for its cultural ecosystem services, while the general public assigns higher importance to regulation ecosystem services. Two monetary measures have been calculated, WTP and WTA. The results indicate no significant differences between WTP and WTA when using a payment card. Participants will pay, on average, 7% of their monthly incomes to protect Vjosa Valley from Hydropower Construction. This study was developed during the pandemic of Covid19, and the results may be affected by the context; however, it represents the first economic evaluation of this rare ecosystem in Albania and Europe.